The Grey Matters: Investigating the Wingfield Strip as an Urban Borderspace - Hope, Julia (School of Architecture, Planning and Geomatics, 2025)
South Africa's refugee policy, favouring urban integration over encampment, has been widely applauded as a progressive measure for refugee protection. While this policy bodes well for visions of inclusive urban citizenship, in practice, refugees and asylum seekers in the country face major barriers to legal and social protection. Many of these barriers are embedded in a local context of inequality and exclusion, particularly in Cape Town, one of the most unequal cities in South Africa. Due to rapid urbanisation and a lack of well-located, affordable housing, a large part of the population is reliant on informal occupancy arrangements. The attempted erasure by the City through criminalisation and eviction of such informality reflects a continuity with the apartheid era's forced removals and influx control laws. Ongoing spatial apartheid in Cape Town, relegating the black urban poor to spatial illegality, affects access to the city for citizens and non-citizens alike. This thesis explores how urban borderspaces, sites of imposing and resisting spatial illegality, produce differentiated urban residents beyond the citizen/non-citizen binary. Placing literature on critical border studies and Southern urbanism in conversation creates an opportunity to grapple with the complexities of urban belonging in interaction with the national border regime. This research endeavour has been theorised through the site of the Wingfield Strip, a highly contested piece of land on the periphery of Kensington, Cape Town. It centres two groups of people living on the Wingfield Strip: an informal settlement of South African citizens called Gate-7, and a supposedly temporary tent of refugees who were forcibly relocated there following their sit-in in the city centre. I have applied an ethnographic methodology. Although the deep fractures within the refugee tent hindered broader community consent and participation, my work at a nearby community centre in Salt River enabled me to build close individual relationships with some of the tent residents. Semi-structured interviews allowed me to explore how the Wingfield Strip is produced and experienced as an urban borderspace by those at the tent and Gate-7. I argue that it is through the fluid imposition of spatial illegality, abandonment and debilitation that the residents of the Wingfield Strip are continually bordered. Working with the Gate-7 residents as a member of an activist group, through participant observation, I was able to investigate the Wingfield residents' shifting legitimacy and differentiation through the lens of infrastructure. I found that the provision and withdrawal of infrastructures of support and control differentially de/legitimises the tent and Gate-7 residents. These processes are navigated and resisted by the residents through practices of insurgent urban citizenships that demand recognition and engender solidarities across the Strip. These findings reveal the limits of and contradictions within existing refugee and urban policy, as well as where insurgent forms of inclusion may be harnessed and protected. This thesis may thus contribute to reimagining belonging in post-apartheid South Africa beyond legal constructions and romantic notions of urban citizenship.